Analisis Data Eksplorasi Dataset Gempa Bumi Indonesia - Rendy Swanda Narastu; Martitus Wiranata; Thomas Arya Lubis; Jadiaman Parhusip (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to perform Exploratory Data Analysis (EDA) on earthquake data in Indonesia obtained from the Meteorology, Climatology, and Geophysics Agency (BMKG). The data used includes earthquake events from November 1, 2008, to January 26, 2023, and contains information such as date, time, latitude, longitude, depth, magnitude, and focal mechanism parameters. In this study, several EDA steps were performed, including calculating descriptive statistics, visualizing the distribution of earthquake magnitudes with histograms, scatter plots for geographical distribution, heatmaps for magnitude distribution patterns based on geographical location, and time series analysis to understand the temporal patterns of earthquake occurrences. Additionally, the earthquake data was visualized on a map using Folium with depth categories in three different colors to facilitate interpretation. The resulting interactive map was also saved as an HTML file to facilitate distribution and further analysis. The results of this study provide a deeper understanding of the characteristics of earthquakes in Indonesia and the existing patterns.